2020
DOI: 10.1038/s41598-020-59250-6
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of bone metabolism by megakaryocytes in a paracrine manner

Abstract: Megakaryocytes (MKs) play key roles in regulating bone metabolism.To test the roles of MK-secreted factors, we investigated whether MK and promegakaryocyte (pro-MK) conditioned media (CM) may affect bone formation and resorption. K562 cell lines were differentiated into mature MKs. Mouse bone marrow macrophages were differentiated into mature osteoclasts, and MC3T3-E1 cells were used for osteoblastic experiments. Bone formation was determined by a calvaria bone formation assay in vivo. Micro-CT analyses were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 39 publications
(44 reference statements)
0
19
0
Order By: Relevance
“…Cell viability was measured using the Cell Counting Kit-8 (CCK-8; Dojindo, Kumamoto, Japan) according to the manufacturer’s instructions. Briefly, 10 μL of WST-8 dye [2-(2-methoxy-4-nitrophenyl)-3-(4-nitrophenyl)-5-(2,4-disulfophenyl)-2H-tetrazolium, monosodium salt] was added to each well of a 96-well plate ( Lee et al, 2020 ). The suspension was incubated for 1 h, and the absorbance was then read at 450 nm with a reference wavelength of 650 nm using a microplate reader (SPECTRAmax 340PC; Molecular Devices, Palo Alto, CA, United States).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell viability was measured using the Cell Counting Kit-8 (CCK-8; Dojindo, Kumamoto, Japan) according to the manufacturer’s instructions. Briefly, 10 μL of WST-8 dye [2-(2-methoxy-4-nitrophenyl)-3-(4-nitrophenyl)-5-(2,4-disulfophenyl)-2H-tetrazolium, monosodium salt] was added to each well of a 96-well plate ( Lee et al, 2020 ). The suspension was incubated for 1 h, and the absorbance was then read at 450 nm with a reference wavelength of 650 nm using a microplate reader (SPECTRAmax 340PC; Molecular Devices, Palo Alto, CA, United States).…”
Section: Methodsmentioning
confidence: 99%
“…After deparaffinization, sections were rehydrated and then stained with either hematoxylin and eosin (H&E, Sigma-Aldrich) following the manufacturer's instructions. Using Image-Pro Plus software (Media Cybernetics, Rockville, MD, United States), bone widths were measured at 5 adjacent locations that were at the same distance from the midline between the sagittal suture and the site of muscle attachment, and their mean values were calculated (Lee et al, 2020). To count the number of osteoblasts, the rehydrated sections were stained with toluidine blue O solution (Sigma-Aldrich), and images of the stained osteoblasts were captured using cellSens Standard BX53 software (Olympus, Tokyo, Japan).…”
Section: In Vivo Calvaria Bone Formationmentioning
confidence: 99%
“…K562 cells were differentiated into mature MKs in phorbol 12-myristate 13-acetate (PMA)-supplemented medium for 7 days [ 26 ]; differentiation was determined by morphological changes, such as an increased nuclear/cytoplasmic ratio, large and multilobulated nuclei, and strong adhesion. Based on several reports that MKs may indirectly contribute to skeletal homeostasis [ 12 , 27 ], we investigated the effects of MK CM on osteoclast differentiation. Using tartrate-resistant acid phosphatase (TRAP) staining, TRAP-positive osteoclasts can be distinguished from TRAP-negative MKs [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Increased MKs in aged mice activate RANKL expression and signaling, thereby promoting osteoclastogenesis and bone resorption activity [ 27 ]. Another study showed that MK CM regulates osteoblast and osteoclast differentiation and increases bone mass in ovariectomized mouse models, although the MK-secreted factors in MK CM have not been identified [ 12 ]. Moreover, the role of MKs in bone metastasis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation